Polymeric nanoparticles targeting Sialyl-Tn in gastric cancer: A live tracking under flow conditions. (December 2022) - Diniz, Francisca; Azevedo, Maria; Sousa, Flávia; Osório, Hugo; Campos, Diana; Sampaio, Paula; Gomes, Joana; Sarmento, Bruno; Reis, Celso A.
Abstract: Drug delivery using nanoparticles (NPs) represents a potential approach for therapy in cancer, such gastric cancer (GC) due to their targeting ability and controlled release properties. The use of advanced nanosystems that deliver anti-cancer drugs specifically to tumor cells may strongly rely on the expression of cancer-associated targets. Glycans aberrantly expressed by cancer cells are attractive targets for such delivery strategy. Sialylated glycans, such as Sialyl-Tn (STn) are aberrantly expressed in several epithelial tumors, including GC, being a potential target for a delivery nanosystem. The aim of this study was the development of NPs surface-functionalized with a specific antibody targeting the STn glycan and further evaluate this nanosystem effectiveness regarding its specificity and recognition capacity. Our results showed that the NPs surface-functionalized with anti-STn antibody efficiently are recognized by cells displaying the cancer-associated STn antigen under static and live cell monitoring flow conditions. This uncovers the potential use of such NPs for drug delivery in cancer. However, flow exposure was disclosed as an important biomechanical parameter to be taken into consideration. Here we presented an innovative and successful methodology to live track the NPs targeting STn antigen under shear stress, simulating the physiological flow. We demonstrate that unspecific binding of NPs agglomerates did not occur under flow conditions, in contrast with static assays. This robust approach can be applied for in vitro drug studies, giving valuable insights for in vivo studies. Graphical abstract: Image 1